2020
DOI: 10.4414/smw.2020.20255
|View full text |Cite
|
Sign up to set email alerts
|

The well-being of Swiss general internal medicine residents

Abstract: BACKGROUND: Physician well-being has an impact on productivity and quality of care. Residency training is a particularly stressful period. OBJECTIVE: To assess the well-being of general internal medicine (GIM) residents and its association with personal and work-related factors. METHODS:We conducted an anonymous electronic survey among GIM residents from 13 Swiss teaching hospitals. We explored the association between a reduced wellbeing (≥5 points based on the Physician Well-Being Index [PWBI]) and personal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 70 publications
0
16
0
6
Order By: Relevance
“…Sharp et al revealed 32% of fellows with positive results for either burnout depressive symptoms had positive results for burnout symptoms and 23% for both burnout and depressive symptoms 18. In contrast, the other three studies indicated no significant association between the use of EMRs and burnout symptoms or reduced well-being 26 30 35. Shanafelt et al showed that the use of EMRs was not associated with burnout in models adjusted for computerised physician order entry and other factors in a group of 6375 participants 26.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Sharp et al revealed 32% of fellows with positive results for either burnout depressive symptoms had positive results for burnout symptoms and 23% for both burnout and depressive symptoms 18. In contrast, the other three studies indicated no significant association between the use of EMRs and burnout symptoms or reduced well-being 26 30 35. Shanafelt et al showed that the use of EMRs was not associated with burnout in models adjusted for computerised physician order entry and other factors in a group of 6375 participants 26.…”
Section: Resultsmentioning
confidence: 98%
“…Eight included studies conducted cross-sectional surveys wherein burnout association with general use of EMRs was investigated 7 18 24–26 29 30 35. Five of the studies showed a positive association between burnout symptoms and EMR use 7 18 24 25 29.…”
Section: Resultsmentioning
confidence: 99%
“…The next generation of physicians is urgently needed [1]. Many residents of the current generation (Generation Y, or Millennials, born 1980 to 1995) are not satisfied with their work-life balance, and they seem to be a vulnerable population regarding mental well-being, burnout, and quitting patient care, as found by various Swiss [2][3][4] and international studies [5][6][7]. A new generation of students, Generation Z (Gen Z, born 1995 to 2010), is becoming the predominant population at university and will join the workforce in a few years' time [8].…”
Section: Introductionmentioning
confidence: 99%
“… 45 When comparing internationally, the percentage was higher than that among general surgery residents in Canada (32.0%) 46 and in the USA (20.0%), 47 and general internal medicine residents in Switzerland (21.0%). 48 Though the percentage-wise prevalence seemed to be higher for our sample than other physician populations, these studies differed in methodology and study period, which could compromise the direct comparability. ‘Low income’ was the most selected (46.11%) major reason chosen for turnover, which was unsurprising given that 75.60% of residents reported annual income level less than 50 000 RMB.…”
Section: Discussionmentioning
confidence: 76%